The Effects of Universal Adhesives on Zirconia/ Resin Composite Shear Bond Strength: Universal adhesives - Klaisiri, Awiruth; Krajangta, Nantawan; Sriamporn, Tool; Thamrongananskul, Niyom (Khon Kaen University Dental Journal, 2019)
The aim of this study was to evaluate the effects of different universal adhesives on zirconia/resin composite shear bond strength. Three universal adhesives [Single Bond Universal (SU), G-Premio bond (GP) and Optibond Universal (OU)], one zirconia primer [Alloy primer (AP)] and one adhesive [Single bond II (SB)] were used in this study. Zirconia disks (6 mm diameter, 4 mm thick) were prepared and embedded in dental gypsum. Specimens were polished and alumina sandblasted for micromechanical retention. The samples were randomly divided into seven groups (N=20 in each group) according to zirconia surfaces treatments for chemical bond: Group1 (No tx), Group2 (AP), Group3 (SB), Group4 (AP+SB), Group5 (SU), Group6 (GP) and Group7 (OU). An Ultradent template (2 mm diameter, 2 mm thick) was placed on top of treated zirconia surface. The resin composite was filled into the mold and then light-cured for 40 seconds. All bonded specimens were kept in distilled water at 37oC for 24 hours and they were subjected to shear bond strength measurement using a universal testing machine at a crosshead speed of 0.5 mm/min. The data were statistically analyzed using one-way ANOVA and Tukey’s test (α=0.05). The shear bond strengths of Group1 to Group 7 were 3.35(1.87), 16.29(2.05), 9.84(2.21), 24.05(1.66), 23.73(2.00), 23.47(2.52) and 22.91(2.19) MPa, respectively. The bond strengths of Group4-7 were significantly higher than those of Group1-3 (p<0.05). However, Group1 showed the lowest bond strength (p<0.05). In conclusion, the universal adhesive may be alternative to the zirconia primer for zirconia surface treatment before repair with resin composite.